(untitled) (Revista Brasileira Multidisciplinar, 2011)
Methodological Research. The event, sponsored by the Master’s Program in Regional Development and Environment - Uniara in partnership with the National Institute of Colonization and Agrarian Reform - INCRA, was aimed at researchers, graduate students and graduate students, government officials, civil society and the private sector. The objective of the forum was to promote discussions about problems related to the challenges of multi and interdisciplinary research, disseminate research and experiences in the area for the scientific community and society, and articulate professionals and institutions for future partnerships. With a total of 160 participants and 37 papers presented, the event had the participation of different public and private institutions, including: State University IV Forum of Regional Development and Environment: theoretical and methodological aspects of research presentation Paulista - UNESP (Araraquara , Rio Claro and Jaboticabal); Support Service for Micro and Small Companies - Sebrae-SP; School of São Carlos, University of São Paulo - EESC-USP (São Carlos); Federal University of São Carlos - UFSCar (San Carlos); University of São Paulo - USP (São Paulo); Integrated College Logatti (Araraquara-SP); University of Campinas - Unicamp (Campinas-SP); Municipal Environment (Araraquara-SP); Brazilian Agricultural Research Corporation - Embrapa (CampinasSP); Department Autonomous Water and Sewage - Daae-Araraquara / SP; Foundation Institute of São Paulo State Land - Itesp. It should be noted that this was the third edition of the forum, which has maintained its annual basis. The classified summaries are published below.